Clinical trials in older people: are we being ageist?. (March 2012) - Crome, Peter
The next few decades will witness a large increase in the number of older people in the population, principally those aged 80 and over. This age group also has the highest prevalence of disease and disability. Therefore, one might expect that the evidence base on how best to treat this group would be well established, but this is not the case. Older people, especially those with physical and mental health comorbidities, continue to be unjustifiably excluded from clinical trials[1, 2] . This raises the question as to whether the exclusion of older people from such investigations can be considered as ageist and whether, as a consequence, older people suffer from age discrimination